1997
DOI: 10.1007/bf01980496
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, structural and acidic characterization of some vanadyl phosphate materials modified with trivalent metal cations

Abstract: A set of new materials with general formula [M(H20)]x(VO)l_xPO4-2H20 (M 3+-A1, Cr, Ga, Mn), isomorphous with layered tetragonal VOPO4.2H20 and having potential catalytic properties, have been characterized by TG and DTA, X-ray diffraction and surface acid strength. During heating the compounds transform in the monohydrated and anhydrous phases, all maintaining a layered structure, with a proper interlayer spacing. Catalytic tests performed with 1-butene show that the M3+-vanadyl phosphates greatly improve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The assignments of the characteristic reflections are made comparing the patterns with the available data with an ICDD (29-0715) card. Such results were also reported by Wang et al [6] and Benes et al [23]. Samples prepared by carbohydrazide, urea, hexamethylenetetramine and oxalyl dihydrazide were completely amorphous.…”
Section: Resultssupporting
confidence: 89%
“…The assignments of the characteristic reflections are made comparing the patterns with the available data with an ICDD (29-0715) card. Such results were also reported by Wang et al [6] and Benes et al [23]. Samples prepared by carbohydrazide, urea, hexamethylenetetramine and oxalyl dihydrazide were completely amorphous.…”
Section: Resultssupporting
confidence: 89%
“…M 3? -modified vanadyl phosphates were tested as precursors of catalysts for 1-butene isomerization [47], ammonia oxidation [48], ammoxidation of toluene [49], selective oxidation of 5-hydroxymethyl-2-furaldehyde to furan-2,5-dicarboxaldehyde [50], oxidative dehydrogenation of ethane [51], and transesterification of soybean oil [5].…”
Section: Vanadyl Phosphatesmentioning
confidence: 99%
“…Moreover, it has been previously reported that the acidity of VOP can be modified by isomorphous substitution of some VO 3+ groups with trivalent metals M 3+ such as Fe 3+ , Cr 3+ , Ga 3+ , Mn 3+ and Al 3+ . These vanadyl phosphate derivatives of general formula M x VO 1Àx PO 4 Á2H 2 O are characterized by a stronger Lewis acidity with respect to VOP itself [28,30] and show an improved catalytic activity [25,28]. Therefore, in the present paper vanadyl phosphate-based catalysts, containing different trivalent metal ions in partial substitution of VO 3+ will be checked in the dehydration of both fructose and inulin to HMF in aqueous solution.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, cubic zirconium pyrophosphate and g-titanium phosphate offered the best performances, in terms of both activity and selectivity, displaying yields to HMF never up to now reached with other heterogeneous catalysts under similar conditions (TOF up to 9 mmol of HMF/g cat h). In this context, vanadyl phosphate VOPO 4 Á2H 2 O (VOP) which is a layered material used in catalytic reactions involving Brönsted and Lewis acid sites, like dehydration [23], hydrocarbon oxidation [24][25][26][27] and isomerization [28], appeared to be promising catalyst to be adopted for the dehydration of carbohydrates to HMF. Thus, the dehydration of both fructose and inuline in aqueous solution was performed using VOP-based catalysts and the preliminary results were patented by us [29].…”
Section: Introductionmentioning
confidence: 99%